THE CLINICAL PICTURE AND COURSE OF TUBERCULOSIS IN CHILDREN WITH PERINATAL HIV INFECTION - S. N. Shugaeva; A. G. Petrova (Туберкулез и болезни лёгких, 2014)
Examinations were made in 125 children, including 65 with tuberculosis and perinatal HIV infection (a continuous sample) and 60 with tuberculosis (a paired sample). The tuberculous process developing in the presence of perinatal HIV infection was manifested by a more marked progression with the registration of the disseminated and complicated forms of tuberculosis, the high frequency of pathogenic dissemination. Adherence to and timely start of antiretroviral therapy contributed to the predominant formation of tuberculous processes within the lymphatic system in most children and to the adequate time of regression of tuberculous changes. The natural course of HIV infection aggravates the tuberculous process, favors the development of disseminated, including generalized, forms, substantially decreases the efficiency of antituberculosis therapy, and is an important predictor of mortality.